2022
DOI: 10.1111/ajt.16931
|View full text |Cite
|
Sign up to set email alerts
|

An updated estimate of posttransplant survival after implementation of the new donor heart allocation policy

Abstract: The Organ Procurement and Transplantation Network (OPTN) implemented a new donor heart allocation policy on October 18, 2018.Studies evaluating the impact of this new policy on posttransplant survival contain discrepant findings. 1 Five reports found decreased posttransplant survival under the new policy, 2-6 and two reports found no difference in posttransplant survival. 7,8 Notably, the studies with lower estimates of posttransplant survival in the post-policy era have significantly fewer follow-up observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 19 publications
(48 reference statements)
0
23
0
Order By: Relevance
“…9,10 Additionally, recent work has demonstrated the importance of evaluating adequate followup between the old and new allocation system, and demonstrated no difference in one-year post-transplant survival under the new allocation system. 11 This study has limitations that are common to retrospective database evaluation. The UNOS dataset is populated by transplant centers and lacks important variables which may affect decisions regarding transplant listing and waitlist management.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…9,10 Additionally, recent work has demonstrated the importance of evaluating adequate followup between the old and new allocation system, and demonstrated no difference in one-year post-transplant survival under the new allocation system. 11 This study has limitations that are common to retrospective database evaluation. The UNOS dataset is populated by transplant centers and lacks important variables which may affect decisions regarding transplant listing and waitlist management.…”
Section: Discussionmentioning
confidence: 97%
“…Prior studies have demonstrated variable results on post‐transplant outcomes under the new allocation system 9,10 . Additionally, recent work has demonstrated the importance of evaluating adequate follow‐up between the old and new allocation system, and demonstrated no difference in one‐year post‐transplant survival under the new allocation system 11 …”
Section: Discussionmentioning
confidence: 99%
“…In this issue of AJT, Lazenby and colleagues used data from the Scientific Registry of Transplant Recipients (SRTR) to assess changes to post‐transplant mortality following implementation of the 2018 heart allocation policy change 2 …”
Section: Figurementioning
confidence: 99%
“…Body mass index (BMI) has previously been shown to affect transplant listing strategy, 1 and was associated with increased waitlist mortality, 1,2 longer wait times before transplantation, 2 and decreased post‐transplant survival 2–4 . In 2018, the United Network of Organ Sharing (UNOS) provided significant changes to the heart transplant allocation system, which resulted in changes in listing strategies (increase in temporary mechanical support and decrease in durable ventricular assist devices), decrease in waitlist times, and variable effects on post‐transplant survival 5–11 . BMI may have significant effects on decisions regarding listing strategy and the use of mechanical support, which may affect waitlist times and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] In 2018, the United Network of Organ Sharing (UNOS) provided significant changes to the heart transplant allocation system, which resulted in changes in listing strategies (increase in temporary mechanical support and decrease in durable ventricular assist devices), decrease in waitlist times, and variable effects on post-transplant survival. [5][6][7][8][9][10][11] BMI may have significant effects on decisions regarding listing strategy and the use of mechanical support, which may affect waitlist times and outcomes. As the impact of BMI on these outcomes under the new allocation system have not been well characterized, we sought to evaluate the role of BMI on listing strategy, waitlist outcomes, and post-transplant outcomes in the current era.…”
Section: Introductionmentioning
confidence: 99%